Sphincter of Oddi dysfunction Type III: New studies suggest new approaches are needed - Wilcox, C Mel (World J Gastroenterol, 2015)
Sphincter of Oddi dysfunction (SOD) has been classified into three types based upon the presence or absence of objective findings including liver test abnormalities and bile duct dilatation. Type III is the most controversial and is classified as biliary type pain in the absence of any these objective findings. Many prior studies have shown that the clinical response to endoscopic therapy is higher based upon the presence of these objective criteria. However, there has been variable correlation of the manometry findings to outcome after endoscopic therapy. Nevertheless, manometry and sphincterotomy has been recommended for Type III patients given the overall response rate of 33%, although the reported response rates are highly variable. However, all of the prior data was non-blinded and non-randomized with variable follow-up. The evaluating predictors in SOD study - a prospective randomized blinded sham controlled one year outcome study showed no correlation between manometric findings and outcome after sphincterotomy. Furthermore, patients receiving sham therapy had a statistically significantly better outcome than those undergoing biliary or dual sphincterotomy. This study calls into question the whole concept of SOD Type III and, based upon prior physiologic studies, one can suggest that SOD Type III likely represents a right upper quadrant functional abdominal pain syndrome and should be treated as such.